Serotonin gene polymorphisms and bipolar I disorder: focus on the serotonin transporter. - Mansour, H; Talkowski, M; Wood, J; Pless, L; Bamne, M; Chowdari, K; Allen, M; Bowden, C; Calabrese, J; El-Mallakh, R; Fagiolini, A; Faraone, S; et al. (2005)
The pathogenesis of bipolar disorder may involve, at least in part, aberrations in serotonergic neurotransmission. Hence, serotonergic genes are attractive targets for association studies of bipolar disorder. We have reviewed the literature in this field. It is difficult to synthesize results as only one polymorphism per gene was typically investigated in relatively small samples. Nevertheless, suggestive associations are available for the 5HT2A receptor and the serotonin transporter genes. With the availability of extensive polymorphism data and high throughput genotyping techniques, comprehensive evaluation of these genes using adequately powered samples is warranted. We also report on our investigations of the serotonin transporter, SLC6A4 (17q11.1-q12). An insertion/deletion polymorphism (5HTTLPR) in the promoter region of this gene has been investigated intensively. However, the results have been inconsistent. We reasoned that other polymorphism/s may contribute to the associations and the inconsistencies may be due to variations in linkage disequilibrium (LD) patterns between samples. Therefore, we conducted LD analyses, as well as association and linkage using 12 polymorphisms, including 5HTTLPR. We evaluated two samples. The first sample consisted of 135 US Caucasian nuclear families having a proband with bipolar I disorder (BDI, DSM IV criteria) and available parents. For case-control analyses, the patients from these families were compared with cord blood samples from local Caucasian live births (n = 182). Our second, independent sample was recruited through the Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD, 545 cases, 548 controls). No significant associations were detected at the individual polymorphism or haplotype level using the case-control or family-based analyses. Our analyses do not support association between SLC6A4 and BDI families. Further studies using sub-groups of BDI are worthwhile.